2013
DOI: 10.2147/opth.s41047
|View full text |Cite
|
Sign up to set email alerts
|

A study of static, kinetic, and dynamic visual acuity in 102 Japanese professional baseball players

Abstract: BackgroundIt seemed that visual functions might have some effects on the performance of baseball players. We measured static, kinetic, and dynamic visual acuity (SVA, KVA, and DVA, respectively) of Japanese professional baseball players to ascertain whether there would be any difference in SVA, KVA, and DVA among player groups stratified according to their performance level.MethodsThe subjects were 102 male professional baseball players with a mean age of 26 years who were members of a Japanese professional ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…Perhaps because it is the base parameter for almost all visual skills, visual acuity is one of the most studied visual attributes in the area of sports vision. Hoshina et al in 2013 studied 102 Japanese professional baseball players and found there were no differences in static visual acuity between the different competitive levels of the athletes. In the current study, visual acuity values were found to be similar to those found in the study by Hoshina et al and do not differ from the results presented for other non‐athlete populations …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps because it is the base parameter for almost all visual skills, visual acuity is one of the most studied visual attributes in the area of sports vision. Hoshina et al in 2013 studied 102 Japanese professional baseball players and found there were no differences in static visual acuity between the different competitive levels of the athletes. In the current study, visual acuity values were found to be similar to those found in the study by Hoshina et al and do not differ from the results presented for other non‐athlete populations …”
Section: Discussionmentioning
confidence: 99%
“…The application of vision sciences to sports is a more recent addition, and is still somewhat scant apart from a few exceptions . Even though visual demand depends on the sport that is practised, some visual skills are fundamental in almost every sport, such as static and dynamic visual acuity, contrast sensitivity, stereopsis, peripheral perception and visual motor reaction time …”
mentioning
confidence: 99%
“…where and/or when the eyes are looking) may differ between elite individuals from different sports [ 10 , 11 ] or between players in different positions in the same sports (e.g. fielders and pitchers in baseball [ 12 ], hitters and pitchers in baseball [ 13 ]; but see [ 14 ]). One interpretation of these findings is that excellent vision has contributed to the potential for ‘eliteness’.…”
Section: Introductionmentioning
confidence: 99%
“…which of the many different tests of vision are used to evaluate vision). While visual acuity (the ability to resolve static, black letters of decreasing size on a white background) is the most well-known measure of acuteness of vision, there are many measures that reflect different visual abilities; these include stereoacuity, visual acuity for dynamic targets (‘dynamic VA’) [ 4 , 12 , 36 ], contrast sensitivity [ 37 ], and positional acuity [ 38 ], to name but a few. Different measures of vision may reflect, to a greater or lesser extent, the demands associated with particular tasks on the field of play.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic VA (KVA) is the ability to identify approaching objects, whereas the ability to identify objects moving horizontally or vertically is called dynamic VA 14. There have been only a few investigations of KVA, and detailed studies have not been conducted on factors influencing differences in KVA ability.…”
Section: Introductionmentioning
confidence: 99%